Total intravenous anesthesia with alfaxalone, dexmedetomidine and remifentanil in healthy foals undergoing abdominal surgery. (May 2019) - Jones, Teela; Bracamonte, José L.; Ambros, Barbara; Duke-Novakovski, Tanya
Abstract: Objective: To evaluate effects of anesthesia induced with alfaxalone and maintained with alfaxalone, dexmedetomidine and remifentanil infusions in foals. Study design: Prospective, experimental study. Animals: A group of six healthy foals [median (range) 11 (8–33) days] undergoing abdominal surgery. Methods: Intravenous (IV) dexmedetomidine (3–7 μg kg −1 ) provided sedation for insertion of a pulmonary artery catheter. IV anesthesia was induced with alfaxalone (2 mg kg −1 ) and maintained with alfaxalone (6 mg kg −1  hour −1 ), dexmedetomidine (1 μg kg −1  hour −1 ) and remifentanil (3 μg kg −1  hour −1 ). Foals were endotracheally intubated and lungs were mechanically ventilated with oxygen. Cardiac output (thermodilution), heart rate and systemic arterial pressure were measured. Arterial and mixed venous blood was analyzed for PO2 and PCO2, and glucose, lactate and electrolyte concentrations. Anesthetic depth was subjectively assessed. Systemic vascular resistance (SVR), oxygen utilization and intrapulmonary shunt were calculated. Preinduction (PB) or 10 minutes postinduction (+10B) data were used as baselines with one-way analysis of variance for repeated measures. Data are mean ± standard deviation; significance was p ≤ 0.05. Results: Duration of anesthesia was 129 ± 22 minutes. One foal was administered additional alfaxalone (0.5 mg kg −1 ) following induction. Cardiac index decreased to 107 ± 31 and 87 ± 21 mL kg −1  minute −1 at 60 and 80 minutes, respectively, compared with PB (157 ± 33 mL kg −1  minute −1 ). SVR increased to 1223 ± 166 dynes second −1  cm −5 at 80 minutes compared with +10B (704 ± 247 dynes second −1  cm −5 ). Mean arterial pressures were 63–128 mmHg. Time from stopping infusions to standing was 46–106 minutes. All foals were hypothermic (<36 °C) and three foals were administered atipamezole (0.05 mg kg −1 ) intramuscularly during recovery. Conclusion: and clinical relevance Combined alfaxalone–dexmedetomidine–remifentanil provided suitable anesthesia to permit laparotomy in foals. At the doses evaluated, prolonged recovery may occur.